Research on incentive mechanism for IoT based on mobile hotspot sharing - Huaizhe LIU; Lin GAO (物联网学报)
Many devices in the Internet of things,especially energy-constrained sensor devices,often lack efficient network connectivity.If the networking method based on mobile hotspot sharing is adopted,large-area network coverage can be realized efficiently.The basic idea of the networking mode is to activate some mobile node in the cellular network (such as the holders of smart phones and other smart devices) to open mobile hotspot,provide Wi-Fi connections for resource-constrained node,and satisfy the communication needs of these node,so as to achieve efficient access to the mobile Internet.In this networking mode,how to encourage mobile users to contribute hotspot is the key.The incentive mechanism in mobile hotspot sharing network and the impact on network performance was studied mainly,and a novel incentive mechanism was designed to enable some users to obtain certain benefits by contributing Wi-Fi hotspot.Firstly,the optimal sharing decision of different types of users under the incentive mechanism and the influence of decision-making among different users were studied.Then,the evolution of user behavior,the overall state of the network with time and the equilibrium state of the system were analyzed.The simulation results show that under the equilibrium state of the system,the number of mobile hotspot contributors increases with the increase of free traffic ratio,which also leads to an increase in the number of hotspot.If the price of unit traffic is too high,the number of users will be reduced,which is not conducive to the operation of the network.In addition,compared with the non-hotspot sharing network,if the mobile hotspot sharing networking mode is adopted,the network performance can be increased by up to 148%.